Impact of Different Suturing Techniques used to from Neopharynx on Postop Pharyngocutaneous Fistula Development after total Laryngectomy - Zahra Aleem, Bakht Aziz, M. Atiq U Rehman, M. Umair Wahab, Irshad Malik, Kashif Iqbal Malik, Hasnain Haider, Maryam Umar (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Laryngeal cancers are the second most common cancers in aero digestive tract. In advanced laryngeal cancers total laryngectomy is performed and it gives excellent results post operatively as the 5 year survival rate is 95%. One of the most common complication of total laryngectomy is formation of pharyngocutaneous fistula post operatively. Aim: To compare interrupted vs continuous suturing technique in formation of neopharynx after total laryngectomy in order to find out which technique is better in terms of pharyngocutaneous fistula formation postoperatively. Method: A total of 20 patients requiring total laryngectomy were selected. Patients were segregated into two groups. patients in group A underwent continuous suturing technique and those in group B underwent interrupted suturing technique in formation of neopharynx. Patients were then post operatively monitored for pharyngocutaneous fistula formation for 10 post operative days Result: Mean age in group-a patients was 56.90±12.94 year and 54.60±9.31 year in group-b patients. Pharyngocutaneous fistula developed in 2(20%) patients with interrupted suturing technique and in 7(70%) patients with continuous suturing technique used for formation of neopharynx. Conclusion: Hence it was concluded from our research that formation of neophaynx per operatively using interrupted suturing technique has less incidence of pharyngocutaneous fistula formation postoperatively then continuous suturing technique as it provides more strength to the wall of neopharynx and has less chances of dehiscence.